Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Aktivitas Belajar Peserta Didik SMA Negeri 12 Makassar - Diana, Nur; Nurhayati, Nurhayati; Supri, Supri (Indonesian Journal of Pedagogical and Social Sciences, 2025)
Abstract. This research aims to find out whether the application of the Problem Based Learning learning model improves student learning activities and student learning outcomes. This type of research is Collaborative Classroom Action Research (PTK). The subjects in this research were students in class XI Science 8 at SMA Negeri 12 Makassar for the 2023/2024 academic year with a total of 39 students. The data collection instruments used in this research were learning activity observation sheets and physics learning results tests which were analyzed using descriptive statistics. This research was carried out in 2 cycles. The results of the research show that the percentage of students' overall learning activities has increased at each stage of the cycle. From this research it can be concluded that the application of the problem based learning model has been able to increase the learning activities of students, especially class XI IPA 8 SMA Negeri 12 Makassar. Keywords: Problem Based Learning, Learning Activities, learning outcomes